A metal organic framework reduces thrombus formation and platelet aggregation ex vivo. Issue 3 (September 2018) - Roberts, Teryn R.; Neufeld, Megan J.; Meledeo, Michael A.; Cap, Andrew P.; Cancio, Leopoldo C.; Reynolds, Melissa M.; Batchinsky, Andriy I.
Abstract : BACKGROUND: Management of hemostasis is a key challenge during extracorporeal life support (ECLS). Metal organic frameworks are being investigated for use as nitric oxide (NO) catalysts for incorporation into ECLS circuitry to prevent thrombosis at the blood–biomaterial interface. A specific metal organic framework, CuBTTri, has been shown to accelerate NO release from bioavailable donors like S -nitrosoglutathione (GSNO). We hypothesized that CuBTTri would reduce thrombus formation in whole blood (WB) and inhibit platelet aggregation. METHODS: CuBTTri particles were added to WB and analyzed by thromboelastography. Biostable metal-based frameworks (MIL-100, Zeolite USY) were added to blood as controls, in addition to a saline vehicle control. Reaction time (R), clot formation time (K), alpha-angle, clot strength (MA), and percent fibrinolysis (LY30/LY60) were recorded. The effect of CuBTTri on platelet aggregation was assessed in WB and platelet-rich plasma (PRP), both with and without addition of GSNO. RESULTS: CuBTTri significantly prolonged R and K and decreased alpha-angle and MA relative to the metal framework controls. Dose escalation results suggest that the control metal-based particles induce thrombus formation, as R and K were significantly reduced compared with the saline control; however, this did not occur in the CuBTTri group. LY30/LY60 were elevated in the CuBTTri group versus saline ( p = 0.014) but were not different from metal framework controls. CuBTTri alone and with GSNO reduced platelet aggregation in WB ( p < 0.0001), whereas GSNO alone had no effect. In PRP, GSNO and CuBTTri inhibited platelet aggregation separately, and together decreased aggregation by 35% relative to GSNO alone ( p = 0.004). CONCLUSIONS: CuBTTri reduced thrombus formation and inhibited platelet aggregation. CuBTTri enhanced platelet inhibition with GSNO, which was consistent with reports that CuBTTri accelerates NO release from endogenous NO donors. This initial characterization of CuBTTri demonstrated its potential as an antithrombogenic agent to be further evaluated with incorporation into ECLS circuitry. Abstract : Supplemental digital content is available in the text.